PENGARUH AGRESIVITAS PAJAK PADA CORPORATE SOCIAL RESPONSIBILITY DENGAN LIKUIDITAS SEBAGAI VARIABEL PEMODERASI - Candra Dewi, Ida Ayu Agung Wahyuning; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2017)
The company usually do the tax aggressiveness for minimizing the tax payment of the company. The company that do tax aggressiveness will tend to do corporate social responsibility (CSR) disclosure is greater  that aims to  gain legitimacy of the society. The research has a purpose to know the effect of tax aggressiveness on CSR with liquidity as the moderating variable. The total of the samples is  81 observation are determined based on non-probability sampling method with purposive sampling technique. Moderated Regression Analysis (MRA) is an analytical technique that used in this research. The result founded that tax aggressiveness take effect on CSR, and the liquidity can not moderating  the effect of tax aggressiveness on CSR.
Keywords: legitimacy theory, corporate social responsibility, tax aggressiveness, liquidity